Phonetic Features of Possessive Additionals In Uzbekistan, Turkish, Kazakh, Azerbaijan And Uygur States - Hamrayev Ilgor Aktamovich; Mardonova Sugdiyana Nasibillo qizi (International Journal Of Literature And Languages, 2025)
In this article, the phonetic phenomena of possessive suffixes used in the Uzbek, Turkish, Kazakh, Azerbaijani, and Uyghur languages are examined and briefly analyzed. Particular attention is paid to phonetic processes observed in certain lexical items. The phonetic system of possessive suffixes in the Uzbek language is theoretically analyzed on the basis of both formal and semantic approaches. Within the framework of formal grammar, the study investigates the morphological features, affixal forms, and grammatical categories expressed through the phonetics of possessive suffixes. From the semantic perspective, the syntactic role of possessive suffixes in sentence structure, their semantic load, and their context-dependent variability are analyzed. These approaches are compared with one another, and their respective advantages in revealing the structure of the Uzbek language system are highlighted. The research findings confirm the significance of the integrated application of these approaches in the theoretical analysis of the Uzbek, Turkish, Kazakh, Azerbaijani, and Uyghur languages, thereby contributing to the broader field of linguistics.